2016
DOI: 10.1002/chem.201602735
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Oxidative‐Addition Pathways of Phenyl Chloride in the Presence of PdIIAbnormal N‐Heterocyclic Carbene Complexes: A DFT Study

Abstract: DFT calculations were performed to elucidate the oxidative addition mechanism of the dimeric palladium(II) abnormal N-heterocyclic carbene complex 2 in the presence of phenyl chloride and NaOMe base under the framework of a Suzuki-Miyaura cross-coupling reaction. Pre-catalyst 2 undergoes facile, NaOMe-assisted dissociation, which led to monomeric palladium(II) species 5, 6, and 7, each of them independently capable of initiating oxidative addition reactions with PhCl. Thereafter, three different mechanistic ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 150 publications
(88 reference statements)
4
19
0
Order By: Relevance
“…To assess the role of the base and the impact of countercations on the transmetalation and reductive elimination events, we considered only the favorable pathway in the presence/absence of different countercations, as depicted in Scheme . Maintaining some similarity with our previous studies, pathways A, B, and C involve the Pd IV intermediates I A , I B , and I C , respectively, deriving from the oxidative addition reactions (Scheme ) . We previously reported that the dimethoxy Pd II complex is the active species, because a stoichiometric amount of base will convert the relatively unstable 10 B and 10 C species into 10 A (Δ G L S‐D3 ( 10 A / 10 B / 10 C )=0.0/9.3/22.0 kcal mol −1 ) .…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…To assess the role of the base and the impact of countercations on the transmetalation and reductive elimination events, we considered only the favorable pathway in the presence/absence of different countercations, as depicted in Scheme . Maintaining some similarity with our previous studies, pathways A, B, and C involve the Pd IV intermediates I A , I B , and I C , respectively, deriving from the oxidative addition reactions (Scheme ) . We previously reported that the dimethoxy Pd II complex is the active species, because a stoichiometric amount of base will convert the relatively unstable 10 B and 10 C species into 10 A (Δ G L S‐D3 ( 10 A / 10 B / 10 C )=0.0/9.3/22.0 kcal mol −1 ) .…”
Section: Resultssupporting
confidence: 72%
“…Recently, we performed DFT calculations to investigate the mechanism of the oxidative addition of PhCl to a model variant ( 1 M ) of the cyclometalated dimeric Pd II complex 1 (see Scheme ). Our study suggested that the dimeric Pd II complex used in the experiments readily transforms into its active monomeric Pd II form through a base‐assisted decomposition mechanism, as outlined in Scheme . It was also found that the less observed and uncommon Pd II /Pd IV pathway is more favorable than the frequently observed classical Pd 0 /Pd II route.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…Since aryl-aryl bond forming cross-couplings are mechanistically quite similar, in our studies on enantioselective coupling we concentrated on the Suzuki-Miyaura reaction, which is usually applied as a method of first choice. The mechanics of the nonstereocontrolled Suzuki-Miyaura (and a few other couplings) reaction catalysed by complexes of nonchelating monophosphines has been studied in detail (Scheme 1) [20][21][22][23][24][25][26][27][28][29] and can be extrapolated to reactions catalysed by transition metal complexes of different types and to stereoselective transformations. At …”
Section: Introductionmentioning
confidence: 99%